Penggunaan Video Animasi Pembelajaran dengan Pendekatan Kontekstual Terhadap Kemampuan Literasi Numerasi Siswa - Lailatul Mufidah; Annafi Awantagusnik (FKIP Universitas Mataram, 2026)
Numeracy literacy is an important competency that must be developed in 21st-century learning, particularly in the Independent Curriculum, which emphasizes contextual understanding and the application of knowledge in real life. This study aims to determine the use of animated learning videos with a contextual approach to improving students' numeracy literacy skills. This study used a quantitative method with a quasi-experimental method using a Pretest-Posttest Control Group Design. The research subjects consisted of two classes VII at MTs Miftahul Ulum, namely class VIIA as the control class (14 students) which used conventional learning, and class VIIB as the experimental class (15 students) which used animated learning videos with a contextual approach.Data were collected through pre-tests and post-tests, then analyzed using the Shapiro–Wilk normality test, Levene's homogeneity test, and the Paired Sample T-Test using SPSS version 25. The analysis results showed that all data were normally distributed and homogeneous. There was a significant increase between pre-test and post-test scores in both classes, with a higher increase in the experimental class. Thus, the use of animated learning videos with a contextual approach has a positive and significant effect on students' numeracy literacy skills. Keywords: animated video; contextual approach; numeracy literacy; mathematics learning.